Impact of a premature menopause on cognitive function in later life. (7th May 2014) - Ryan, J; Scali, J; Carrière, I; Amieva, H; Rouaud, O; Berr, C; Ritchie, K; Ancelin, M‐L
<x xml:space="preserve">Abstract</x> Objective To determine whether premature menopause (≤40 years) can have long‐lasting effects on later‐life cognition and investigate whether this association varies depending on the type of menopause and use of hormone treatment (HT). Design Population‐based cohort study. Setting The French Three‐City Study. Population Four thousand eight hundred and sixty‐eight women aged at least 65 years. Methods Multivariable‐adjusted logistic regression models were used to determine the association between age at menopause, type of menopause (surgical, natural), and the use of menopausal HT and later‐life cognitive function. Main outcome measures Performance on a cognitive test battery (at baseline and over 7 years) and clinical dementia diagnosis. Results Menopause at or before the age of 40 years, both premature bilateral ovariectomy and premature ovarian failure (non‐surgical loss of ovarian function), was associated with worse verbal fluency (OR 1.56, 95%CI 1.12–1.87, P = 0.004) and visual memory (OR 1.39, 95%CI 1.09–1.77, P = 0.007) in later life. HT at the time of premature menopause appeared beneficial for later‐life visual memory but increased the risk of poor verbal fluency. Type of menopause was not significantly associated with cognitive function. Premature menopause was associated with a 30% increased risk of decline in psychomotor speed and global cognitive function over 7 years. Conclusion Both premature surgical menopause and premature ovarian failure were associated with long‐term negative effects on cognitive function, which are not entirely offset by menopausal HT. In terms of surgical menopause, these results suggest that the potential long‐term effects on cognitive function should form part of the risk/benefit ratio when considering ovariectomy in younger women.